Bibliometric Analysis of Literature on Psychological Stress and Head and Neck Cancer (1977-2025) (Bangladesh Journal of Medical Science, 2026)
Psychological stress has been increasingly recognized as an important factor influencing quality of life (QoL), treatment response, and overall outcomes in patients with head and neck cancer (HNC). This bibliometric study provides a comprehensive overview of literature exploring the relationship between psychological stress and HNC from 1987 to 2025. The data were retrieved from the Dimensions database, analyzed using the Biblioshiny application of the R package, and reported according to the GLOBAL guidelines for bibliometric reporting. A total of 206 articles met the inclusion criteria. Results showed a steady increase in publications over time, with an annual growth rate of 7.39% and an average of 23.53 citations per document. The USA led in publication output and citation impact. The most relevant journals were Supportive Care in Cancer and Head & Neck, indicating an integration of psychosocial aspects within oncology research. The thematic analysis based on keywords demonstrates an integration of clinical oncology with psychosocial, suggesting a transition toward holistic, patientcentered cancer care. Highly cited articles were focused on psychological distress, the psychosocial impact of treatment, and the importance of supportive interventions for both patients and caregivers. Although research exploring the link between psychological stress and HNC has been ongoing for many years, the overall volume of published studies remains low. The findings underscore the need for research in low- and middleincome countries and stronger cross-disciplinary partnerships in the psycho-oncology, medical, and psychological domains for the holistic care of cancer patients. This study contributes to the understanding of psychosocial research in HNC patients and offers directions for future efforts to integrate psychological care into comprehensive cancer management.BJMS, Vol. 25 No. 01 January’26 Page : 14-27